Analisis Bibliografi Koleksi Perpustakaan Nasional Republik Indonesia Terkait Palestina-Israel - Nasution, Muhammad Ansyari Tantawi; Zahra, Siti Fatimatuz (Perpustakaan Nasional, 2024)
This research aims to carry out bibliographic analysis based on scientific subject, creator, year of publication and author as well as filtering relevant works from the collections held by the National Library of Indonesia related to the Palestine-Israel conflict. The keywords used are